![{4}^{x + 1} - {4}^{x - 1} = 60 {4}^{x + 1} - {4}^{x - 1} = 60](https://tex.z-dn.net/?f=+%7B4%7D%5E%7Bx+%2B+1%7D+++-+++%7B4%7D%5E%7Bx+-+1%7D++%3D+60)
equação exponencial, por favor me explique as etapas
Soluções para a tarefa
Respondido por
3
Explicação passo-a-passo:
4^(x+1) -4^(x-1)=60
4^x .4^1 - 4^x . 4^-1=60
4^x.( 4^1 -4^-1)=60
4^x.(4-1/4)=60
4^x.(15/4)=60
4^x.(15)=4.(60)
4^x.(15)=240
4^x=240/15
4^x=16
4^x=4^2
x=2
Nattih:
Não se transforma em y não?
Respondido por
1
Explicação passo-a-passo:
Perguntas interessantes
Geografia,
10 meses atrás
Português,
10 meses atrás
Matemática,
10 meses atrás
Biologia,
1 ano atrás
História,
1 ano atrás